A reassessment of frequency and vocabulary size in L2 vocabulary teaching - Schmitt, Norbert; Schmitt, Diane (Cambridge University Press, 2014)
The high-frequency vocabulary of English has traditionally been thought to consist of the 2,000 most frequent word families, and low-frequency vocabulary as that beyond the 10,000 frequency level. This paper argues that these boundaries should be reassessed on pedagogic grounds. Based on a number of perspectives (including frequency and acquisition studies, the amount of vocabulary necessary for English usage, the range of graded readers, and dictionary defining vocabulary), we argue that high-frequency English vocabulary should include the most frequent 3,000 word families. We also propose that the low-frequency vocabulary boundary should be lowered to the 9,000 level, on the basis that 8–9,000 word families are sufficient to provide the lexical resources necessary to be able to read a wide range of authentic texts (Nation 2006). We label the vocabulary between high-frequency (3,000) and low-frequency (9,000+) as mid-frequency vocabulary. We illustrate the necessity of mid-frequency vocabulary for proficient language use, and make some initial suggestions for research addressing the pedagogical challenge raised by mid-frequency vocabulary.